Wybrane aspekty prawne zapewnienia bezpieczeństwa imprez masowych jako jednego z warunków bezpieczeństwa publicznego - Wykrent, Dariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article presents some aspects of the legal system in Poland relating generally to the complex issues of security, and in particular to the specific — due to the form and features of occurrence — security of mass events. Starting from the existing literature in terms of security and public safety, the article discusses the constitutional and statutory regulations, including those related to them, some interpretations and case law, with particular reference to the law on mass events security.
Keywords: imprezy masowe; bezpieczeństwo; aspekty prawne; bezpieczeństwo publiczne